1996
DOI: 10.1021/jp9601678
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic Microelectrodes. The Microstrip Electrode:  Theory and Experiment

Abstract: Theory is presented to predict the mass transport limited current flowing at a hydrodynamic microstrip electrode located in a rectangular flow cell under steady state and chronoamperometric conditions. The influence of electrode size is quantified with the relative effects of lateral diffusion, normal diffusion, and axial convection identified. Theory is found to be in good agreement with experimental measurements conducted using the oxidation of tris(4-bromophenyl)amine at a platinum microstrip electrode. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…However, Aixill et al [22] demonstrated the good agreement between the theory to predict the current at a micro-strip electrode taking into account the lateral diffusion, normal diffusion and axial convection and the experimental results obtained with a home-made cell with platinum strips as working electrodes and the oxidation of tris(4-bromophenyl)amine in continuous flow-cells. The results show an enhanced mass transport characteristic compared with equivalent macro-electrodes.…”
Section: Introductionmentioning
confidence: 97%
“…However, Aixill et al [22] demonstrated the good agreement between the theory to predict the current at a micro-strip electrode taking into account the lateral diffusion, normal diffusion and axial convection and the experimental results obtained with a home-made cell with platinum strips as working electrodes and the oxidation of tris(4-bromophenyl)amine in continuous flow-cells. The results show an enhanced mass transport characteristic compared with equivalent macro-electrodes.…”
Section: Introductionmentioning
confidence: 97%
“…Hydrodynamic devices have been employed for an enormous variety of applications in recent years, including mechanistic investigations and analytical detection. [1][2][3][4][5] In the field of electrochemistry, tools such as the rotating disc, 6 channel, 1 and wall-jet electrodes 3 have provided key insights into properties such as the composition and chemical and photochemical reactivity of molecules in fluid solution. 7,8 However, despite their undoubted success, these hydrodynamic tools share a number of common limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrodynamic devices have been employed for an enormous variety of applications in recent years, including mechanistic investigations and analytical detection. In the field of electrochemistry, tools such as the rotating disc, channel, and wall-jet electrodes 3 have provided key insights into properties such as the composition and chemical and photochemical reactivity of molecules in fluid solution. , However, despite their undoubted success, these hydrodynamic tools share a number of common limitations. One of the most significant of these is the inability to mix reagents in a well-defined way close to the detector.…”
Section: Introductionmentioning
confidence: 99%
“…Three electrode geometries were selected, (i) a macroelectrode (ii) a microband electrode, 8 and (iii) a microstrip electrode, 16 and each was situated within a channel flow cell (Figure 1). For each geometry the mass transport limited current/flow rate behavior calculated using the FE method was compared to that predicted using alternative finite difference methods.…”
Section: Introductionmentioning
confidence: 99%